Electric field interference and bimodal particle translocation in nano-integrated multipores. Issue 16 (22nd February 2019) - Tsutsui, Makusu; Yokota, Kazumichi; Nakada, Tomoko; Arima, Akihide; Tonomura, Wataru; Taniguchi, Masateru; Washio, Takashi; Kawai, Tomoji
Abstract : Parallel integration of multiple channels is a fundamental strategy for high-throughput particle detection in solid-state nanopores wherein understanding and control of crosstalk is an important issue for the post resistive pulse analysis. Abstract : Parallel integration of multiple channels is a fundamental strategy for high-throughput particle detection in solid-state nanopores wherein understanding and control of crosstalk is an important issue for the post resistive pulse analysis. Here we report on a prominent effect of cross-channel electric field interference on the ionic current blockade by nanoparticles in nano-spaced pore arrays in a thin Si3 N4 membrane. We systematically investigated the variations in resistive pulse profiles in multipore systems of various inter-channel distances. Although each pore acted independently when they were formed at excessively far distances, we observed significant cross-pore electrostatic interactions under close-integration that led the multipores to virtually act as a single-pore of equivalent area. As a result of the interference, the resistive pulse height demonstrated bimodal distributions due to the pronounced particle trajectory-dependence of the ionic blockade effects. Most importantly, the overcrowded multi-channel structure was found to deliver significant crosstalk with serious degradation of the sensor sensitivity to particle sizes. The present results provide a guide to design multipore structures regarding the trade-off between the detection throughput and sensor sensitivity.